English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

FIRST COMPLETE.
#1. X TO THE SECOND+9X+18=(X+3)(X+__)
#2.Q TO THE SECOND+3Q-18=(Q-3)(Q+__)

fACTOR THESE
#3 Y TO THE SECOND+6Y+8
#4 W TO THE SECOND+6W+5
#5 Q TO THE SECOND-18Q+45
#6 H TO THE SECOND+16H-17
#7 P TO THE SECOND+3P-54
CHOOSE THE CORRECT FACTORING FOR THIS EXPRESSION.
#8 X TO THE SECOND+8XY+15Y TO THE SECOND
FACTOR THIS EXPRESSION
#9 M TO THE SECOND-3MN-54N TO THE SECOND

FACTOR EACH TRINOMIAL.
#10 T TO THE EIGHT +5+ TO THE 4TH -24
#11 P TO THE 6TH+14P TO THE 3RD-72

FIRST PEROSN TO ANSWER ALL THESE WILL GET REWARDED FOR THE BEST ANSWER SO HURRY

2007-03-29 14:38:18 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

i agree with forestpirate...
dont be lazy.. solve it first by yourself and you can ask people here if it's right or wrong and people will then help you...
it's also a way for you to learn... dont just depend on others or else you'll fail in your exam.. believe me..

dont get me wrong.. it's just a piece of advice.. think twice..

2007-03-31 19:44:22 · answer #1 · answered by kishimii 2 · 0 0

1. x^2 + 9x + 18 = (x +3) (x + 6)
2. q^2 + 3q - 18 = (q - 3)(q + 6)
3. y^2 + 6y + 8 = (y + 2)(y + 4)
4. w^2 + 6w + 5 = (w + 5)(w + 1)
5. q^2 - 18q + 45 = (q - 3)(q - 15)
6. h^2 + 16h - 17 = (h + 17)(h - 1)
7. p^2 + 3p - 54 = (p + 9)(p - 6)
8. x^2 + 8xy + 15y^2 = (x + 5y)(x + 3y)
9. m^2 - 3mn - 54n^2 = (m - 9n)(m + 6n)
10. t^8 + 5t^4 - 24 = (t^4 + 8)(t^4 - 3)
11. p^6 + 14p^3 - 72 = (p^3 + 18)(p^3 - 4)
or (p^3 + 18)(p^3/2 - 2)(p^3/2 + 2)

2007-03-29 22:01:22 · answer #2 · answered by rooster1981 4 · 0 0

Please take off Caps Lock.

1. x^2 + 9x + 18 = (x+3) (x+6)
2. q^2 + 3q - 18 = (q-3) (q+6)

3. y^2 + 6y + 8 = (y+2) (y+4)
4. w^2 + 6w + 5 = (w+5)(w+1)
5. q^2 - 18q + 45 = (q-15)(q-3)
6. h^2 + 16h - 17 = (h+17)(h-1)
7. p^2 + 3p - 54 = (p+9)(p-6)

8. x^2 + 8xy + 15y^2 = (x+3y)(x+5y)
9. m^2 - 3mn - 54n^2 = (m-9n)(m+6n)

10. t^8 + 5t^4 - 24 = (t^4 - 1)(t^4 + 6)
= (t^2 - 1)(t^2 + 1)(t^4 + 6)
= (t-1)(t+1)(t^2+1)(t^4+6)

11. p^6 + 14p^3 - 72 = (p^3 + 18)(p^3 - 4)
These can be factored further, but only with lots of cube root signs.

2007-03-29 21:45:47 · answer #3 · answered by Scarlet Manuka 7 · 0 0

Question #12:

Why can't you solve these yourself? Once you solve them then you can post your answers and ask us if they are right.

2007-03-29 21:42:22 · answer #4 · answered by forestpirate 3 · 1 0

Yes I can... will I? No, I don't have time to do random work when I have to do my own.

2007-03-29 21:46:50 · answer #5 · answered by Silent J 3 · 2 0

fedest.com, questions and answers